Thymus‐derived regulatory T cells restrain pro‐inflammatory Th1 responses by downregulating CD70 on dendritic cells. (18th March 2015) - Dhainaut, Maxime; Coquerelle, Caroline; Uzureau, Sophie; Denoeud, Julie; Acolty, Valérie; Oldenhove, Guillaume; Galuppo, Adrien; Sparwasser, Tim; Thielemans, Kris; Pays, Etienne; Yagita, Hideo; Borst, Jannie; et al.
Abstract The severity and intensity of autoimmune disease in immune dysregulation, polyendocrinopathy, enteropathy, X‐linked (IPEX) patients and in scurfy mice emphasize the critical role played by thymus‐derived regulatory T cells (tTregs) in maintaining peripheral immune tolerance. However, although tTregs are critical to prevent lethal autoimmunity and excessive inflammatory responses, their suppressive mechanism remains elusive. Here, we demonstrate that tTregs selectively inhibit CD27/CD70‐dependent Th1 priming, while leaving the IL‐12‐dependent pathway unaffected. Immunized mice depleted of tTregs showed an increased response of IFN‐γ‐secreting CD4+ T cells that was strictly reliant on a functional CD27/CD70 pathway. In vitro studies revealed that tTregs downregulate CD70 from the plasma membrane of dendritic cells (DCs) in a CD27‐dependent manner. CD70 downregulation required contact between Tregs and DCs and resulted in endocytosis of CD27 and CD70 into the DC. These findings reveal a novel mechanism by which tTregs can maintain tolerance or prevent excessive, proinflammatory Th1 responses.